2005
DOI: 10.1111/j.1440-1754.2005.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

The ketogenic diet in refractory childhood epilepsy

Abstract: The KD is an effective treatment for some children with refractory epilepsy, being generally well tolerated and rarely associated with side-effects. Response is not necessarily predicted by age, syndrome or aetiology. A prospective study of the KD is presently underway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Other potential side effects can result from vitamin and mineral deficiencies secondary to restricting carbohydrates, including osteopenia and osteoporosis (Bergqvist et al, 2008, Cervenka and Kossoff, 2013, Mackay et al, 2005), although the precise mechanism remains unclear and possibly hormone-related (Zengin et al, 2015). The standard practice of supplementing a recommended daily allowance of multivitamin and mineral supplements can prevent such deficiencies.…”
Section: Adverse Effects Compliance and Appropriate Managementmentioning
confidence: 99%
“…Other potential side effects can result from vitamin and mineral deficiencies secondary to restricting carbohydrates, including osteopenia and osteoporosis (Bergqvist et al, 2008, Cervenka and Kossoff, 2013, Mackay et al, 2005), although the precise mechanism remains unclear and possibly hormone-related (Zengin et al, 2015). The standard practice of supplementing a recommended daily allowance of multivitamin and mineral supplements can prevent such deficiencies.…”
Section: Adverse Effects Compliance and Appropriate Managementmentioning
confidence: 99%
“…27 Anticonvulsive effects of different patterns of caloric restrictions were usually observed after a few months. 28 Previous investigations revealed that restricted caloric intake increases GABA tone of the brain, either directly, by enhancing the synthesis of the glutamic acid decarboxylase and, thus, GABA synthesis in the brain, 29 or indirectly, by increasing the levels of the serum ketone body β-hydroxybutyrate. 8 In contrast to our results, short-term application of a PF-diet in rats did not protect neurons against excitatory damages of pilocarpine injections.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, very low carbohydrate diets that induce ketosis have been shown to lead to reductions in serum triglycerides, low-density lipoprotein and total cholesterol and increased levels of high-density lipoprotein cholesterol in adults [9]. Other potential side effects can result from vitamin and mineral deficiencies secondary to restricting carbohydrates and prolonged ketonemia, including osteopenia and osteoporosis [3,126,127], although the precise mechanism remains unclear. The standard practice of supplementing a recommended daily allowance of multivitamin and mineral supplements can reduce the risk of such deficiencies.…”
Section: Management Of Adverse Effects and Poor Compliance In Adultsmentioning
confidence: 99%